UPAYA MENINGKATKAN PEMAHAMAN KONSEP DAN DISPOSISI MATEMATIS MENGGUNAKAN MODEL PEMBELAJARAN TREFFINGER DI SMA NEGERI 1 ANGKOLA BARAT - Benny Sofyan Samosir; Andes Fuady Harahap (Universitas Muhammadiyah Tapanuli Selatan, 2018)
his type of research is Class Action Research. Where the subject of the research is the grade X5 SMA Negeri 1 Angkola West which consists of 38 students. While the techniques and tools to capture data that is now, tests and observations. The percentage of students on mathematical disposition now cycle I was 50.26% to 81.57% in cycle II. With the amount of the percentage increase in students ' mathematical disposition of 31.31%. Understanding of the mathematical concepts of students increases, it is retrieved from the percentage of the cycle I 52.63% become 81.39% in cycle II, students and the amount of the percentage rose 28.94%. Students learn math activity increases; it is retrieved from 63.98% percentage of the cycle I and 63.98% in cycle II. With the amount of the percentage increase in the activity of students of 22.94%. The ability of the teacher to manage learning percentage amounted to 64.00% in cycle I and cycle II 83.00%, with an increase of 19.00%. The results of this study showed that the learning model Treffinger might improve the understanding of mathematical concepts and disposition of the students of class X5 SMA Negeri 1 Angkola West.Keywords: The Learning Model Treffinger, understanding Mathematical concepts, Dispositions, SPLDV.